Political Melodrama Meets Domestic Fiction: The Politics of Genre in North and South. - KUCICH, JOHN (Novel: A Forum on Fiction, 2019)
Generic innovation has the potential to create strong new frameworks for political discourse. Elizabeth Gaskell's North and South hybridizes two nineteenth-century narrative genres--political melodrama and domestic fiction--to invite readerly involvement in the creation of new narratives of political reform. The novel "relocates" the conventions of these two genres, transplanting the formal, thematic, and rhetorical conventions of each genre to the plotlines and subject matter of the other. Such relocation undermines normative expectations about both genres and opens possibilities for new kinds of stories about social conflict. North and South exploits generic dissonance to encourage creative political engagement, stressing the urgency of reform but without fixed expectations about its outcome. Gaskell makes generic relocation possible by defamiliarizing both genres, exposing their intrinsic limitationswhile calling attention to the newconceptualwork each genre's conventions might perform in unexpected narrative contexts. In its approach to generic hybridization, North and South typifies Condition of England novels, which routinely relocate existing generic conventions of many kinds--the bildungsroman, the regional novel, crime fiction, the roman a' clef, the biblical allegory. Transplanting conventions from these various genres into narrative contexts where they seem not to belong, Condition of England novels exploit generic dissonance as an instrument of open-ended literary and political regeneration. Condition of England novels were the first group of literary texts to call on readers to participate at the national level in social reform, and generic dissonance played a key role in that literary and political act of inclusion.